Pengaruh Disiplin Kerja Dan Budaya Kerja Terhadap Produktivitas Kerja Pegawai Pada Dinas Kesehatan Kota Depok - Maulida Hildayanti; Riri Oktarini (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to determine the effect of work discipline and work culture on employee productivity at Depok Municipal Health Office, both partially and simultaneously. This research uses quantitative research type methods. The population of this study was 121 employees and the sampling technique used was through statistical calculations using the slovin formula so that a sample of 93 employees was obtained. While the primary data collection technique through a questionnaire which is processed using the SPSS version 26 application system. The analysis method used in this research is regression analysis, determination analysis, t-test and f-test. Based on the results of t test research, it is obtained that the tcount for work discipline is 10.624> t table 1.986 with a significant level of 0.000 <0.05, which means that partially there is a significant effect of work discipline on employees' work productivity. And the tcount for work culture is 12.215> t table 1.986 with a significant level of 0.000 <0.05, meaning that partially there is a significant influence work culture on employee productivity. For the f-test, Fcount is 87.891> Ftable 3.10 with a significant level of 0.000 <0.05, which means that there is simultaneously a significant effect of work discipline and work culture on employee productivity. Multiple linear regression analysis yielded the equation Y = 8.887 + 0.300 (X1) + 0.491 (X2). Determination analysis obtained a value of 0.813 with a percentage of 66.1%, while the rest is influenced by other variables